The Business Élite and Municipal Politics in Vancouver 1886-1914 - McDonald, Robert (Urban History Review / Revue d'histoire urbaine, 1983)
This paper explores the direct and indirect involvement of top businessmen in Vancouver municipal politics from 1886 to 1914. It emphasizes the divergent political aims and roles of large and small entrepreneurs. In Vancouver, unlike Winnipeg, small businessmen rather than the business élite controlled municipal politics. The Vancouver business élite's direct participation in civic politics and indirect influence over municipal decision making were both circumscribed after the initial city-founding period by several factors: business pressures mounted as Vancouver's economy became regionally based, forcing top businessmen to devote their undivided attention to business affairs; limited legislative benefits were to be derived by leading businessmen from formal participation in the day-to-day administration of local government; and voters' deference to business élite views declined once the city's institutional structure had been organized. A government reform movement, aimed at reasserting élite influence in civic politics, was less successful in Vancouver than in many other American and Canadian centres because Vancouver's underlying economic, social and political conditions made reform less necessary.